Clinical Competence Among Inpatient Nurses: A Comparative Study Across Two Indonesian Tertiary Hospitals - Raul Requilmy Suprapto; Nurfika Asmaningrum; Anisah Ardiana; Dicky Endrian Kurniawan; Elok Faradisa; Thi Thu Huong Phan (Nursing and Health Sciences Journal (NHSJ), 2026)
Clinical competence is a fundamental indicator of the quality of nursing care and patient safety. In Jember Regency, type C hospitals such as Kalisat Regional General Hospital and Balung Regional General Hospital play an important role in providing health services in their respective areas. However, differences in unit characteristics and resource management can lead to variations in nursing competence. Objective: This study aims to compare the clinical competence of inpatient nurses between RSD Kalisat and RSD Balung. Methods: This is a comparative descriptive study with a cross-sectional design. The population consisted of inpatient nurses, with a total sample of 64 respondents (32 from each hospital) through total sampling. Data were collected using the Clinical Competency Questionnaire (CCQ) and analyzed using the Independent Sample T-test and Mann-Whitney U test. Results: The findings showed no significant difference in overall clinical competence between the two hospitals (p=0.757). The same was true for each unit tested in both hospitals (general p=0.549), (surgery p=0.190), and (internal medicine p=0.626). Conclusion: In general, the clinical competence of nurses in both hospitals and between units had equivalent values and showed consistent standards. Recommendation: Hospitals should continue to provide ongoing training to maintain and improve clinical competence and other competencies.